Research Methods for Education With Technology: Four Concerns, Examples, and Recommendations - Wright, Daniel B. (Frontiers in Education, 2019)
The success of education with technology research is in part because the field draws upon theories and methods from multiple disciplines. However, drawing upon multiple disciplines has drawbacks because sometimes the methodological expertise of each discipline is not applied when researchers conduct studies outside of their research training. The focus here is on research using methods drawn largely from psychology, for example, evaluating the impact of different systems on how students perform. The methodological concerns discussed are: low power; not using multilevel modeling; dichotomization; and inaccurate reporting of the numeric statistics. Examples are drawn from a recent set of proceedings. Recommendations, which are applicable throughout the social sciences, are made for each of these.